Comparisonal Analysis of Financial Performance before and During the Covid-19 Pandemic at the Blud of the Atma Husada Mahakam Regional Mental Hospital in Samarinda - Hadi Machbudiansyah; Ardi Paminto; Yana Ulfah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Financial performance is a measure of the success of an organization, especially in public institutions such as the BLUD of the Atma Husada Mahakam Regional Mental Hospital in Samarinda, its role as an institution in providing health services for the community related to the soul or mental. Financial performance is measured by using Financial Ratios, especially at regional hospitals in their financial management through the Regional Public Service Agency (BLUD) it is recommended to follow the guidelines of the Director General of Treasury Regulation Number PER-36/PB/2016. Currently, almost countries in the world, including Indonesia, are experiencing the Covid-19 Pandemic or Corona Virus, where this disease can cause exposure to the virus and cause death. Therefore, a hospital is needed as a Covid referral in the area. However, The purpose of this study is to prove the difference in financial performance before Covid 19 and during Covid 19 at the BLUD of the Atma Husada Mahakam Regional Mental Hospital in Samarinda, East Kalimantan. This type of research uses descriptive methods with a comparison approach. The object in this study is the BLUD of Regional Mental Hospital Atma Husada Mahakam Samarinda. The results in this study indicate that financial performance during the Covid 19 period was lower than before Covid 19.